IMPLEMENTASI PERATURAN DAERAH KABUPATEN LANGKAT TENTANG BANTUAN HUKUM BAGI MASYARAKAT MISKIN DALAM MEWUJUDKAN AKSES TERHADAP KEADILAN - Grace Mayma Idolways Sinurat (SUAN PUBLISHER, 2026)
Access to justice for people experiencing poverty cannot be secured by legal norms alone. It requires a policy that is translated into legal services that target groups can know, reach, and use. Langkat Regency enacted Regional Regulation Number 6 of 2024 on Legal Aid for Poor Communities. This study examines the implementation of the regulation and its relevance to access to justice. The research is designed as empirical legal research using a qualitative case-study strategy. George C. Edward III's implementation framework is employed to examine communication, resources, disposition, and bureaucratic structure, while the access-to-justice perspective is used to assess information accessibility, service availability, procedural accessibility, and the ability of beneficiaries to use legal mechanisms. At the current manuscript stage, the analysis relies on legislation, official statistics, government documents, legal aid organization data, and court institutional information. Documentary evidence indicates an initial implementation foundation through the enactment of the regional regulation, documented outreach activities in 2025, the formal role of the Langkat Regency Legal Division, and the presence of an accredited legal aid organization in Langkat. Nevertheless, these indicators are insufficient to establish substantive effectiveness. The available materials do not yet provide verified evidence on beneficiary coverage, local budget realization, application-processing time, rejected applications, geographic distribution of services, or the lived experience of poor legal-aid users. The article therefore distinguishes formal policy implementation from experienced access to justice. It argues that implementation should be evaluated through measurable service indicators and users' experiences rather than the existence of regulation and outreach activities alone.